The Effect of Managerial Ability on the Market Valuation of Unrecognized Tax Benefits - Chunhao Xu; Xiangge Wang; Shiyou Li; Rachana Kalelkar; Lili Gai (American Business Review, 2024)
This study examines the effect of managerial ability on the market valuation of unrecognized tax benefits (UTBs). While UTBs are generally associated with significant risks, we hypothesize that highly able managers can enhance the market valuation of the UTBs through their ability and efforts to report high-quality UTBs and retain the economic benefits of tax strategies. Consistent with our expectations, we find that managerial ability positively moderates the relationship between UTBs and firm values. Our additional analyses show that highly able executives can reduce firms’ future overall tax risk and tax settlements. Collectively, our findings suggest that the stock market values UTBs positively in firms managed by highly capable executives who can minimize tax risks while lowering tax payments.